David J. Brewer : the life of a Supreme Court justice, 1837-1910 - Brodhead, Michael J. (Carbondale : Southern Illinois University Press, 1994)
This informative new book is the first biography of David J. Brewer, an Associate Justice of the United States Supreme Court from 1889 to 1910 and certainly one of the most visible judges of his time. Michael J. Brodhead's candid account covers Brewer's entire judicial career as well as his childhood, education, personal life, and many and varied public activities. Prior to rising to the nation's highest tribunal, Brewer served as a county probate judge, a state district judge, a Kansas State Supreme Court justice, and a federal circuit court judge. He was known not only for his long tenure on the Supreme Court but also for his numerous off-the-bench statements as an orator and writer.
Many of Brewer's judicial opinions and nonjudicial utterances created controversy, particularly when he confronted the reform issues of his day. The court presided over by Chief Justice Melville W. Fuller has been seen as reactionary, determined to infuse the law with social Darwinism and laissez-faire ideology. Further, the Fuller Court has been accused of hindering all legislation that might have improved the economic and social condition of the American masses. Yet, contrary to these usual assessments of the Fuller Court as a whole, Brewer accepted most of his generation's reform goals. He championed many forms of social legislation, the regulation of business, the rights of women and minorities, educational reform, and world peace.
Brodhead contends that until recently historians have carelessly and inaccurately created a false image of Brewer, partly by citing a small sample of his opinions and public statements as representative of his alleged conservatism. They have also assumed that the disputable decisions of Brewer and his contemporaries were based on ideological predilections and that precedent and established legal principles played no role. During his term, Brewer was the author of such notable court cases as In re Debs, Muller v. Oregon, and Kansas v. Colorado. He supported property rights, admired honest entrepreneurial activity, and opposed the concentration of power in any form. He favored the individual in all instances, whether that individual was the initiator of a great economic enterprise or a farmer struggling to extend agriculture into the western plains.
The path to the bench: from Smyrna to Kansas, 1837-1862 -- Judge and citizen: Leavenworth, 1863-1870 -- "A coterie of able men": Brewer and the Kansas Supreme Court on corporations, the public interest, politics, and crime, 1871-1884 -- The substance of right: Brewer and the Kansas Supreme Court on prohibition, family law, women's rights, race questions, and the legal profession, 1871-1884 -- "An empire in itself": the Eighth Circuit, 1884-1889 -- A centennial justice: elevation to the united states supreme court -- The court and the economic realm: regulation, public finance, trusts, patents, and land, 1890-1900 -- The court and humanity: minorities, labor, crime, and legal ethics, 1890-1900 -- Rostrum and fireside: off-the-bench activity, 1890-1900 -- Rates, trusts, and taxes: the court and the commerce, police, and taxing powers, 1901-1910 -- Facts and law: responses to reform, 1901-1910.
Includes bibliographical references (pages 239-252) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Brewer, David J. -- 1837-1910.; United States. -- Supreme Court -- Biography; États-Unis. -- Supreme Court -- Biographies; Brewer, David J. -- 1837-1910; United States. -- Supreme Court; Judges -- United States -- Biography; Juges -- États-Unis -- Biographies; LAW -- Government -- Federal; POLITICAL SCIENCE -- Government -- Judicial Branch; LAW -- Legal Services; LAW -- Civil Procedure; BIOGRAPHY & AUTOBIOGRAPHY -- Lawyers & Judges; Judges; United States; Law - U.S.; Law, Politics & Government; Law - U.S. - General; dissertations; Biographies; Academic theses; Thèses et écrits académiques.